Comparative analysis of bio-inspired and topology-optimized lattices under compressive loading - Ahmad Anas Arifin; I Made Londen Batan; Michele Bici; Arif Wahjudi; Agus Sigit Pramono (Teknomekanik, 2026)
Lattice structure design is still dominated by strut-based forms and surface-based shapes, such as triply periodic minimal surfaces (TPMS), which both exhibit overlapping limitations. Strut lattices often show strong anisotropy because their response depends heavily on cell orientation, while TPMS lattices are difficult to adjust when bounded by geometric constraints. These conditions eventually led to stagnation in the development of lattice morphology. Hybrid and topology-optimization methods have appeared as possible alternatives, but many of them still produce modified versions of classical patterns. This study examined two lattice geometries: the Pyramorph, inspired by the shape of a pyramid, and the Topomorph, generated through a topology optimization framework. Both structures were designed using a CAD unit cell patterning technique and manufactured using the FDM method, with relative densities ranging from 0.40 to 0.44. Their mechanical behaviour was examined through FEA simulation and uniaxial compression testing. The parameter variations included cell orientations of 0°, 15°, 30°, and 45°, and cell sizes of 8 mm and 12 mm within a 24 mm specimen. The Topomorph showed superior strength, reaching 15–20 MPa, while the Pyramorph reached only 7–8 MPa. The highest value, about 20.5 MPa, was obtained from the Topomorph at 0° and with an 8 mm cell size. Failure modes indicated buckling and delamination in the Pyramorph, while the Topomorph tended to collapse progressively. These findings indicate that topology optimization combined with CAD-based patterning could significantly improve lattice performance.